The Strategies in Using K-W-L to Improve the Students' Reading Comprehension Achievement - Pratama, Anantyo Jantera; Tasnim, Zakiyah; Sundari, Siti (English Education Study Program, 2023)
This study aimed to improve the seventh-grade students’ reading comprehension achievement by using K-W-L strategy at SMPN 2 Kunir Lumajang. Classroom action research design was used in this study with the 30 students of 7C class in SMPN 2 Kunir Lumajang as the research participants. The data was collected by using reading comprehension test to know the improvement of reading comprehension achievement and using classroom observation field note to know the strengths and weaknesses of the action. The criterion of success is at least 75% of the students got the minimum score of 65 in the test. The findings revealed that K-W-L strategy improves the students’ reading comprehension achievement. The students become more active and the activity of brainstorming their background knowledge before reding helps them most to get the gist of the text. Overall, the results imply that K-W-L strategy is good in assisting the students to comprehend the reading text.